Investment psychology explained : - Pring, Martin J. (J. Wiley & Sons, 1993)
Psychology Explained will give you a renewed appreciation of the classic trading principles that, through bull and bear markets, have worked time and again. You'll see, with the help of numerous illustrative examples, what goes into making an effective investor-and how you can work toward achieving that successful profile.